Cetoacidosis diabética normoglucémica en mujeres con diabetes gestacional - Cabrera-Figueredo, Ignacio; Luaces-Sánchez, Plácido; Cruz-Fernández, Celia Yamilet de la; González-Reigada, Alicia (Archivo Médico Camagüey, 2020)
Background: although the majority cases who suffer from diabetic ketoacidosis show with hyperglycemia, occasionally it can be diagnosed with normal values of glycemia especially on pregnant women. Objective: to show two pregnant women without diagnosis of gestational diabetes previously who developed a normoglyacemic diabetic ketoacidosis during pregnancy. Case report: two pregnant women without diagnosis of gestational diabetes previously who are treated with glucocorticoids to induce fetal pulmonary develop and to resolve an acute crisis of asthma respectively and they later developed a normoglyacemic diabetic ketoacidosis. Conclusions: diabetic ketoacidosis during pregnancy happen more frequent on pregnant women without previously diagnosis of pre-gestational diabetes, on few cases it happen on pregnant women who suffer from gestational diabetes in which it shows as a normoglyacemic diabetic ketoacidosis in a low percent. DeCS: DIABETES, GESTATIONAL/diagnosis; DIABETIC KETOACIDOSIS/diagnosis; HYPERGLYCEMIA/diagnosis; PREGNANCY COMPLICATIONS; RISK FACTORS.